1997
DOI: 10.1177/0265407597146008
|View full text |Cite
|
Sign up to set email alerts
|

Differential Accounts of Closeness in Older Adult Sibling Relationships

Abstract: Research into the older adult sibling relationship has only recently recognized and attempted to account for differential feelings of closeness between siblings throughout their lives. Sixty-one participants, aged fifty-four and older with at least two siblings, were interviewed concerning the degree of closeness they felt towards their siblings. Participants in this investigation were able to differentiate levels of closeness felt toward their siblings and account for these differences. Family systems theory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 8 publications
1
16
0
4
Order By: Relevance
“…For instance, researchers have found that similarity influences feelings of closeness in many relationships, and researchers studying adult sibling relationship have found a similar pattern (Folwell et al, 1997). For example, Folwell et al (1997) found that siblings who share similarities in interests were closer than siblings who did not.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, researchers have found that similarity influences feelings of closeness in many relationships, and researchers studying adult sibling relationship have found a similar pattern (Folwell et al, 1997). For example, Folwell et al (1997) found that siblings who share similarities in interests were closer than siblings who did not.…”
Section: Discussionmentioning
confidence: 99%
“…This increased contact between full siblings as compared with stepsiblings could foster more supportive behaviors. Furthermore, research has demonstrated that siblings who are closer in age tend to be closer to one another than siblings of a greater age difference (Folwell, Chung, Nussbaum, Bethea, & Grant, 1997), which could foster the use of socially supportive behaviors. Many half-and stepsibling relationships have a greater variance in the age difference between siblings than full sibling relationships, and twins have no difference in age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we considered characteristics of the sibling relationship prior to parental death. The quality of adult siblings’ relationships at midlife is shaped by the quality and frequency of their interactions earlier in the life course (Folwell et al 1997; Matthews and Rosner 1988). Furthermore, whether one’s aged parent engaged in end-of-life planning may reflect long-standing family dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…However, not only do young adults report different grandparents as being the one to whom they feel closest (Folwell & Grant, 1999a, 1999bThomas, 1995), they also report differential closeness with their set of grandparents (Folwell & Grant, 1999a, 1999bPecchioni & Berkos, 2001). Research indicates that a variety of factors influence reported closeness with grandparents.…”
mentioning
confidence: 99%